(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Given current debates about South Africa’s contested past, how could teacher educators address this issue with preservice teachers so that their historical understanding develops and they present a multi-perspective view of history in practice? The underlying problem this question raises is how to shift teachers’ approaches to history teaching from one that splits “fact” and interpretation in a one-dimensional account, to a multi-perspective view which acknowledges the interrelationship of interpretations and “facts”. This article’s purpose is to reflect on what I learnt for my own practice as a teacher educator after I observed eight practising teachers, who were former preservice teachers, teach an oral history task. The results of this research led me to propose changes to a history methodology course. I suggest firstly that preservice teachers scrutinise claims to “the truth” in oral history accounts through the “sins” of memory, which they use to re-examine “the truth” claims in their personal oral history tasks. Secondly, by exploring major developments in South African historiography, this provides a framework that shows how multi-perspectives arise and how the “politics of interpretation” informs the different “schools” of historiography. This process helps the preservice teachers examine the interrelationship between some of the “big” ideas found in historiography with the “small” ideas in their oral history tasks. It also aims to plant the seeds of doubt about history being a fixed body of knowledge, so that the preservice teachers might present a multi-perspective view of history once they become practising teachers. Adapting this process to their own context could provide a way for teacher educators in other countries to address similar issues with preservice history teachers.